NO and NO2 emissions of waste tire pyrolysis oil (TPO) blended with diesel in a flameless combustor - Chumpitaz, Raul G.; Barbosa, Jean A.; Andrade, Jose C.; Azevedo, Claudia G. [UNESP]; Andrade, Ricardo A.; Coronado, Christian J. R. (Springer, 2022)
Combustion systems can use tire pyrolysis oil (TPO) due to its high energy content. The amount of nitrogen and sulfur present in the TPO should result in NOx and SO2 emissions when combustion occurs. A flameless combustion regime can reduce pollutant emissions, mainly NOx, with greater thermal efficiency. This work aims to analyze the NO and NO2 emission in different diesel fuel mixtures with TPO, 5% (TPO5), and 10% (TPO10) by mass, in a flameless regime. A combustor was used operating with a maximum heat input of 13 kW and an effervescent injector promoting an average Sauter diameter of 33.89 +/- 3.77 mu m. The uniform temperature profile within the combustor characterizes the flameless combustion regime that was reached after 50 min for diesel and after 40 min for TPO5 and TPO10 from the ignition. TPO5 and TPO10 have similar NO emissions in flameless combustion. The NO2 emission increases with the TPO content in the mixture.
Keywords: Pyrolysis oil; Waste tires; Diesel; Flameless; Emissions